#### Answer

m= -3

#### Work Step by Step

We can calculate the slope by $\frac{x_{2}-x_{1}}{y_{2}-y_{1}}$.
By substituting , we get $\frac{-6-3}{2-(-1)}= \frac{-9}{3}= -3$

Chegg costs money, GradeSaver solutions are free!

Published by
Cengage

ISBN 10:
978-1-337-61408-5

ISBN 13:
978-1-33761-408-5

m= -3

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.